Report of a rare case of periaortitis at the aortic arch and successful therapeutic strategy with prednisolone. Issue 5 (November 2019) - Ando, Takashi; Okada, Hiroshi; Takeda, Makoto; Umemoto, Tomio
Abstract: Periaortitis is one of the less common manifestations of the aorta pathology. Periaortitis mostly arises from the outer layers of the abdominal aorta and iliac arteries. However, other large arteries may also be involved, but rarely the thoracic aorta. Here we present a successful conservative treatment using prednisolone therapy for periaortitis of the aortic arch which shows various clinical symptoms. <Learning objective: Periaortitis is one of the less common manifestations of the aorta pathology. Periaortitis rarely has an impact on the thoracic aorta. The treatment strategy for this complication, especially the dose of prednisolone, is not well established. This case report supports documenting periaortitis in the aortic arch. Not only did we begin initial prednisolone treatment at 45 mg/day, but also performed a downward titration after only half a year.>